TIPOLOGI FASAD RUMAH ADAT BATAK TOBA - Sihotang, Koriana M.; Naibaho, Polin DR; Aritonang, Emmy Ria (Unika Santo Thomas, 2019)
Batak Toba’s traditional houses is one of the relics of batak tribe tradition that up to now still many abandon the values of philosophy and beauty and create a natural picture that is considered to have soul. Batak traditional house is a building that characterizes the house or typical of the tribe of Batak which symbolizes the culture and characteristics of the batak community. Discussion in this research about typology facade of traditional Batak Toba house building in Tomok Village, Huta Bolon and Huta Siallagan. Facade typology discussed in this research is the front view, the use of materials, dimensions, the use of color, the placement of doors and windows of traditional houses of Batak Toba in Samosir. The research method usedin this research is qualitative, that is describing the existing condition data of facade design from some custom house of Batak Toba which is located from three different villages namely Tomok Village, Huta Siallagan and Huta Bolon. Data analysis in this qualitative research is to search and arrange systematically data obtained from the results of field notes and documentationby organizing into categories, describing in units, synthesizing, arranging into patterns and making conclusions.